2012
DOI: 10.1016/j.ridd.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

How executive functions are related to intelligence in Williams syndrome

Abstract: Williams syndrome is characterized by impairments in executive functions (EFs). However, it remains unknown how distinct types of EFs relate to intelligence in this syndrome. The present study analyzed performance on working memory, inhibiting and shifting, and its links to IQ in a sample of 17 individuals with WS, and compared them with a group of 17 typically developing individuals matched on chronological age and gender. In conclusion, our results suggest that working memory, inhibiting, and shifting relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
4
11
2
Order By: Relevance
“…This is consistent with findings of Osório et al (2012) who found that IQ significantly moderated working memory and inhibition task performance but failed to find a significant effect for set shifting when comparing children with Williams syndrome and controls. Research with typically developing children suggests that associations between IQ and set shifting performance are complex.…”
Section: Factors That Moderate the Fasd-ef Associationsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings of Osório et al (2012) who found that IQ significantly moderated working memory and inhibition task performance but failed to find a significant effect for set shifting when comparing children with Williams syndrome and controls. Research with typically developing children suggests that associations between IQ and set shifting performance are complex.…”
Section: Factors That Moderate the Fasd-ef Associationsupporting
confidence: 91%
“…Similarly, the IQ of the non-FASD group and IQ difference between groups moderated inhibition findings. Similar to the present findings, Osório et al (2012) also found that IQ significantly moderated working memory and inhibition task performance when comparing children with Williams syndrome (well below average mean IQ) and controls (average mean IQ). Mahone et al (2002) also found a significant difference in inhibitory control performance between children with ADHD and controls, but only for those who had Low Average to Average IQ (i.e., standard score 85 to 109) and not those with High Average IQ (i.e., standard score 110 to 119) or Superior IQ (i.e., standard score>120).…”
Section: Factors That Moderate the Fasd-ef Associationsupporting
confidence: 90%
“…Disagreeing with the fact that only the cognitive profile would be associated with the mnemonic capacity, recent research has indicated that executive function would be the main cause of memory impairment, and should be evaluated with the same attention, especially if taken into account the hypothesis of the relation between behavior and changes in the frontal lobe 30 . Among all executive functions, memory is the aspect that go along with the levels of IQ, as well as variations of IQ 31 .…”
Section: Sleep-wake and Williams-beuren Syndromementioning
confidence: 99%
“…Patients with WBS are generally thought to display a typical cognitive and behavioral profile [14]- [16] characterized by a mild to moderate intellectual disability (mean IQ 56) [16] associated with hyperacusis, severe impairments in visuo-spatial abilities and numeric processing, contrasting with relative good short term verbal memory [17], relative preservation of face processing, great receptivity to music [18], and linguistic and socialaffective skills. The latter abilities often produce a "cocktail party" personality including overfriendliness, lack of fear with strangers, strong pro-social compulsion [19], excessive talkativeness, and verbal fluency with extensive and expressive speech rich in vocabulary at least in adulthood.…”
Section: Introductionmentioning
confidence: 99%